Big data: From beginning to future - Yaqoob, Ibrar; Hashem, Ibrahim Abaker Targio; Gani, Abdullah; Mokhtar, Salimah; Ahmed, Ejaz; Anuar, Nor Badrul; Vasilakos, Athanasios V. (International journal of information management, 2016)
•We use structuralism and functionalism paradigms to analyze the origins of big data applications.•Current trends and sources of big data.•Processing technologies, methods and analysis techniques for big data are compared in detail.•We analyze major challenges with big data and also discussed several opportunities.•Case studies and emerging technologies for big data problems are discussed. Big data is a potential research area receiving considerable attention from academia and IT communities. In the digital world, the amounts of data generated and stored have expanded within a short period of time. Consequently, this fast growing rate of data has created many challenges. In this paper, we use structuralism and functionalism paradigms to analyze the origins of big data applications and its current trends. This paper presents a comprehensive discussion on state-of-the-art big data technologies based on batch and stream data processing. Moreover, strengths and weaknesses of these technologies are analyzed. This study also discusses big data analytics techniques, processing methods, some reported case studies from different vendors, several open research challenges, and the opportunities brought about by big data. The similarities and differences of these techniques and technologies based on important parameters are also investigated. Emerging technologies are recommended as a solution for big data problems.